Shedding Light on the Matter: Evaluating Changing Patterns of Object Dedication in Ionian Sanctuaries (7th/6th – 5th/4th centuries BC) with Lexicometrical Analysis - Loy, Michael; Slawisch, Anja (Journal of Greek Archaeology, 2021)
Reconstructing moments in ancient history is done most effectively when we draw together different types of evidence. Particularly given the fragmentary and random shape of our datasets, many scholars would agree that it is important to combine material – and sometimes patterns only become visible when we do so in new and experimental ways. As scholarship on ancient Greek religion has become increasingly interdisciplinary in recent years, many scholars have brought together datasets long studied separately – the material evidence by archaeologists and anthropologists, and the texts by philologists and philosophers – now is a prime-time to cross-pollenate different types of evidence on a much broader scale. This paper proposes that by bringing together types of evidence that might usually be kept apart and by applying new methodologies, we can shed further light on certain ancient socio-cultural phenomena.